2019
DOI: 10.3390/math7040368
|View full text |Cite
|
Sign up to set email alerts
|

Computing Degree Based Topological Properties of Third Type of Hex-Derived Networks

Abstract: In chemical graph theory, a topological index is a numerical representation of a chemical network, while a topological descriptor correlates certain physicochemical characteristics of underlying chemical compounds besides its chemical representation. The graph plays a vital role in modeling and designing any chemical network. Simonraj et al. derived a new type of graphs, which is named a third type of hex-derived networks. In our work, we discuss the third type of hex-derived networks H D N 3 ( r ) , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Simonraj et al [11] created the new network which is named as third type of hex-derived networks. Chang-Cheng Wei et al [12] found some topological indices of certain new derived networks. In this paper, we compute the exact results for all the above descriptors.…”
Section: Resultsmentioning
confidence: 99%
“…Simonraj et al [11] created the new network which is named as third type of hex-derived networks. Chang-Cheng Wei et al [12] found some topological indices of certain new derived networks. In this paper, we compute the exact results for all the above descriptors.…”
Section: Resultsmentioning
confidence: 99%
“…e novel network, labeled the third category of hexderived networks, was developed in [1]. In [2,3], they defined the graphically construction algorithm for the third type of hexagonal hex-derived network HHDN3(t). Huo el at.…”
Section: Structure Of Third-type Hex-derived Networkmentioning
confidence: 99%
“…With the dimension p, hexagonal networks create hex-derived networks, which have a wide range of implementations in engineering, computer science, and also medicine. In [1], researchers created a new form of graph known as a "third type of hex-derived networks" [2,3] and continued this work by calculating degree-based topological descriptors for these networks, in which they computed exact values of some vertex-edge named topological indices for this network.…”
Section: Introductionmentioning
confidence: 99%
“…In [40], several degree-based topological indices of CHDN3[n] are calculated directly by using formulas of topological indices mentioned in Table 1 We divide the vertex set V of CHDN3[n] into two disjoint parts according to the degree of vertices, as: Also, we divide the edge set E of CHDN3[n] into three disjoint parts based on the degrees of the end vertices of each edge, as follows:…”
Section: Our Contributionmentioning
confidence: 99%